Partial Analysis of Mudharabah Financing on the Profitability of the Sharia Commercial Banks in Indonesia - Jahroh, Siti; Suganda, Asep Dadan (Universitas Alma Ata, 2021)
In order to gain profits, sharia banks as the actors who collect and distribute the fund from and for the people are trying to improve the quality and quantity of their performance, and mudharabah is one of the financing akad in sharia banks. This study aimed to determine the effect of mudharabah financing on the profitability (ROA) at sharia commercial banks (BUS) in Indonesia. The populations in this study were all registered Sharia Commercial Banks in the central bank of Indonesia (BI) with a total of 14 banks. However, from this population, 9 banks were failed to complete the data. This study used a simple linear regression analysis method, the classical assumption test method, and statistical test. The conclusion drawn from the partial testing showed a significant effect with t observe of 2.053. Since the value of t observe 2.053 > t table 2.048, it can be concluded that there was a significant effect of mudharabah financing on the Return on Assets (ROA).